2012
DOI: 10.1038/nnano.2012.64
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of engineered nanoparticles in a municipal solid-waste incineration plant

Abstract: More than 100 million tonnes of municipal solid waste are incinerated worldwide every year 1 . However, little is known about the fate of nanomaterials during incineration, even though the presence of engineered nanoparticles in waste is expected to grow 2 . Here, we show that cerium oxide nanoparticles introduced into a full-scale waste incineration plant bind loosely to solid residues from the combustion process and can be efficiently removed from flue gas using current filter technology. The nanoparticles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
140
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(151 citation statements)
references
References 18 publications
4
140
0
3
Order By: Relevance
“…We believe that the proposed NP electrospray has the potential to be applied to various plant seeds Nadjafi et al, 2006). Meanwhile, environmental friendly NPs (Rieter et al, 2008;Yan et al, 2010) can be employed in the future to alleviate concerns surrounding the cytotoxicity of metal oxide NPs (Walser et al, 2012). In addition, the use of engineered NPs carrying DNA, plant hormones or other chemicals in the proposed process for seed treatment may open up new opportunities for a broad application of nanotechnology in the agricultural industry.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that the proposed NP electrospray has the potential to be applied to various plant seeds Nadjafi et al, 2006). Meanwhile, environmental friendly NPs (Rieter et al, 2008;Yan et al, 2010) can be employed in the future to alleviate concerns surrounding the cytotoxicity of metal oxide NPs (Walser et al, 2012). In addition, the use of engineered NPs carrying DNA, plant hormones or other chemicals in the proposed process for seed treatment may open up new opportunities for a broad application of nanotechnology in the agricultural industry.…”
Section: Resultsmentioning
confidence: 99%
“…This demonstrated by a study in which nanoparticles of cerium oxide was used, introduced the same either before the incineration process as well as the output current of the incinerator furnace gas. These binds weakly to solid waste during the combustion process, although are achieved filtered through current technology, nanoparticles end attached to solid waste entering either landfilled or leaving raw materials, which they have been recovered [55]. The opinion, perception and public acceptance are crucial factors in advancing nanotechnology, so that the development of this technology is parallel to the economic and social impacts.…”
Section: Obstacles To the Adoption Of Nanotechnologymentioning
confidence: 99%
“…A recent study into the incineration of nanomaterials in a waste plant showed that at a variety of different locations within the building, no or only small amounts of nanomaterials were found following their incineration [56]. Whilst this could also be true for nanocellulose, it is safe to assume that, very much like wood, cotton and other raw cellulosic materials from which CNCs are extracted will end in similar ash once burnt.…”
Section: Life-cycle and Human Exposure Of Cncsmentioning
confidence: 99%